Новый вид цестод плосконосого плавунчика - Anomotaenia reticulata sp. n. (Dilepididae) - Спасский, А.А.; Коновалов, Ю,Н, (Вестник зоологии, 1967)
A description of Anomotaenia reticulata of Phalaropus fulicarius from the Chukotka coast of the Bering Sea is given. There are 20-22 hooks, 0.028 mm long, on a rostellum, 16-20 testicles, a cirrussac 0.1-0.12X0.028 mm, an uterus is netlike. The description is accompanied by a detailed differential diagnosis, pictures of a scolex and :segments.